Tradisi Bajapuik pada Adat Perkawinan Masyarakat Pariaman di Kelurahan Talang Mandi Kota Duri - Putri, Yolanda Eka; Kadarisman, Yoskar (Peneliti.net, 2024)
This research was conducted in Talang Mandi Village, Mandau District, Bengkalis Regency with the aim of finding out the process of the bajapuik tradition in Talang Mandi Village and the reasons why overseas people do not use pick-up money. In determining research subjects using criteria determined by the researcher or what is called a purposive technique. This research uses qualitative methods with data collection techniques through interviews and documentation. The number of research subjects was 6 people. The theory used is the Theory of Social Change by Piotr Sztompka. The results of this research are that there are social changes that have occurred in the Pariaman community in Talang Mandi Village, the community no longer uses collection money and does not carry out the bajapuik tradition process in accordance with Pariaman. The changes that occur in the community in Talang Mandi Village are caused by new cultural contacts, people's thinking is increasingly advanced and they do not want to be bound by existing traditions so that people carry out traditional Bajapuik activities according to the abilities of their respective families. In the last 7 years, a very prominent change is because marriages are no longer arranged because of arranged marriages but because of dating so that the bride and groom who want to get married already have an agreement between the two of them before a meeting between the parents or what is called maanta asok is held. Likewise, parents no longer worry about the invitation fee or the actual traditional process.